(untitled) (Universal International Scientific Journal, 2026)
This article is devoted to the issues of psychological training of parataekwondo fighters. Parataekwondo is a sport that requires not only physical training, but also high mental and volitional qualities. The article analyzes the theoretical foundations of psychological training, its types and stages, as well as the psychological characteristics of parataekwondo fighters. It also covers the practical aspects of psychological training of parataekwondo fighters for competitions, psychological problems encountered in them and methods for their elimination. The article gives recommendations on improving the effectiveness of psychological training based on modern research